ANALISIS TUGAS BAGIAN KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH KABUPATEN MAJALENGKA - Dea Qotrunnada Munawaroh; Akhmad Nadirin; Am’mar Abdullah Arfan (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2026)
The People’s Welfare Section of the Regional Secretariat holds a strategic position in supporting policy formulation, inter-agency coordination, program facilitation, and the monitoring and evaluation of public welfare policies. This study examines the implementation of duties performed by the People’s Welfare Section of the Majalengka Regency Regional Secretariat and assesses the support provided by human resources and administrative technology. The study employed a descriptive qualitative approach with an organizational case study design. Data were collected through observation, semi-structured interviews, and document analysis conducted in September 2024 and were analyzed through data condensation, data display, and conclusion drawing. The findings indicate that the People’s Welfare Section has performed functions related to policy preparation, coordination, facilitation, administration, monitoring, and evaluation. Its institutional position is primarily supportive and coordinative rather than that of a direct technical implementer of education, health, social welfare, or public assistance programs. The section is supported by ten employees, comprising five civil servants and five non-civil-service personnel. However, the adequacy of staffing and task distribution still requires systematic job and workload analysis. Technological support has begun to be developed through a web-based administrative system, but its effectiveness cannot yet be established because the system remains under development. Organizational strengthening should therefore focus on task arrangement, staff competency development, procedural standardization, and the integration of technology into existing work processes.